2008
DOI: 10.1002/asi.20794
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking and online search: Lessons learned and challenges ahead

Abstract: , and the third study is described for the first time in this article. These studies reveal how users view the ranked results on a search engine results page (SERP), the relationship between the search result abstracts viewed and those clicked on, and whether gender, search task, or search engine influence these behaviors. In addition, we discuss a key challenge that arose in all three studies that applies to the use of eye tracking in studying online behaviors which is due to the limited support for analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
134
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(149 citation statements)
references
References 26 publications
10
134
1
2
Order By: Relevance
“…search engine manipulation effect | search rankings | Internet influence | voter manipulation | digital bandwagon effect R ecent research has demonstrated that the rankings of search results provided by search engine companies have a dramatic impact on consumer attitudes, preferences, and behavior (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12); this is presumably why North American companies now spend more than 20 billion US dollars annually on efforts to place results at the top of rankings (13,14). Studies using eye-tracking technology have shown that people generally scan search engine results in the order in which the results appear and then fixate on the results that rank highest, even when lower-ranked results are more relevant to their search (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…search engine manipulation effect | search rankings | Internet influence | voter manipulation | digital bandwagon effect R ecent research has demonstrated that the rankings of search results provided by search engine companies have a dramatic impact on consumer attitudes, preferences, and behavior (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12); this is presumably why North American companies now spend more than 20 billion US dollars annually on efforts to place results at the top of rankings (13,14). Studies using eye-tracking technology have shown that people generally scan search engine results in the order in which the results appear and then fixate on the results that rank highest, even when lower-ranked results are more relevant to their search (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Studies using eye-tracking technology have shown that people generally scan search engine results in the order in which the results appear and then fixate on the results that rank highest, even when lower-ranked results are more relevant to their search (1)(2)(3)(4)(5). Higher-ranked links also draw more clicks, and consequently people spend more time on Web pages associated with higher-ranked search results (1)(2)(3)(4)(5)(6)(7)(8)(9). A recent analysis of ∼300 million clicks on one search engine found that 91.5% of those clicks were on the first page of search results, with 32.5% on the first result and 17.6% on the second (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This includes more detailed information about which parts of documents subjects view and if subjects cognitively engage with a particular feature or object even when there is no observable log action such as a click. Lorigo et al [184] provide an overview of eye-tracking and online search and identifies future research directions.…”
Section: Methodsmentioning
confidence: 99%
“…Eye tracking has identified patterns of processing documents, for example an "F" shape reading pattern for a search engine result page (SERP) (Granka, Feusner, & Lorigo, 2006). Granka et al, 2004 andLorigo et al, 2008 studied the number of fixations, their duration and time on task in a user study of searches with the Yahoo! and Google search engines.…”
Section: Eye Movements In Searchmentioning
confidence: 99%